A North-South model of trade with search unemployment - Ignat Stepanok (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
In this paper I build a North-South model of international trade, economic growth and search-frictional unemployment in the North. Growth is driven by a process of creative destruction in the North followed by imitation in the South. I study the effects of intellectual property rights protection and trade liberalization on unemployment and welfare in the North. Intellectual property rights protection decreases unemployment and increases welfare. Trade liberalization increases welfare but has an ambiguous effect on unemployment. It decreases unemployment if workers in the North have a high outside option and increases it if their outside option is low. I provide empirical evidence in support of the last result using data for 20 OECD countries. – – In diesem Artikel wird ein Nord-Süd Modell mit internationalem Handel, endogenemWachstum und Sucharbeitslosigkeit im Norden entwickelt. Schöpferische Zerstörung ist der Wachstumsmotor im Norden und wird von Imitation im Süden gefolgt. Ich untersuche die Effekte des Schutzes des geistigen Eigentums und der Handelsliberalisierung auf Arbeitslosigkeit und Wohlfahrt im Norden. Starker Schutz des geistigen Eigentums reduziert die Arbeitslosigkeit und erhöht das Wohlfahrtsniveau. Handelsliberalisierung erhöht das Wohlfahrtsniveau, während die Wirkung auf die Arbeitslosigkeit nicht eindeutig ist. Die Arbeitslosigkeit fällt, wenn Arbeitnehmer im Norden den Wert der Freizeit hoch schätzen, andernfalls steigt sie. Diese theoretische Schlußfolgerung wird empirisch anhand von Daten aus 20 OECD Staaten unterstützt.
Keywords: F12; F16; F43; J63; O31; O34; O41; 330; creative destruction; search; unemployment; trade liberalization; intellectual property rights; North-South trade